CoSSAT: Code-Switched Speech Annotation Tool - Shah, Sanket; Joshi, Pratik; Sitaram, Sunayana; Santy, Sebastin (EMNLP AnnoNLP workshop, 2019)
Code-switching refers to the alternation of two or more languages in a conversation or utterance and is common in multilingual communities across the world. Building code-switched speech and natural language processing systems are challenging due to the lack of annotated speech and text data. We present a speech annotation interface CoSSAT, which helps annotators transcribe code-switched speech faster, more easily and more accurately than a traditional interface, by displaying candidate words from monolingual speech recognizers. We conduct a user study on the transcription of Hindi-English code-switched speech with 10 annotators and describe quantitative and qualitative results.